Prevalensi dan Tingkat Infeksi Soil Transmitted Helminths Dihubungkan dengan Golongan Usia dan Jenis Kelamin pada 5 Sekolah Dasar - Hardjanti, Ambar; Rachmawati, Putri; Cresnaulan Desiyanti, Titis; Fauzi Rahman, Rizki; Wahyudi, Yudi; Intan Farellina, Yolanda (Lembaga Penelitian Universitas YARSI, 2017)
Soil transmitted helminths (STH) infection is an infectious disease with a high prevalence,especially in developing countries. More than 1.5 billion people or 24% of the world's population are infected with STH. Indonesia is one of 11 countries in Southeast Asia which are declared as endemic for STH infection. Data on the prevalence of STH infection in children in Indonesia is still quite high, namely 60-90%. Meanwhile, infections that occur continuously will reduce the quality of human resources, especially children. This study was conducted with the aim to determine the prevalence and level of STH infection in children of primary school age, and to find out whether there is a relationship between the prevalence and rate of STH infection with age and sex. This research was conducted in 5 State Elementary Schools (SD) located in Jakarta, Bekasi and Serang (Banten) in 2016. This study used analytical cross sectional method. Samples in the form of feces of students int he 5 state elementary schools. Stool samples collected were 61 from SDN Tanah Tinggi 01 PagiCentral Jakarta, 57 from SDN Pondok Bambu 04 Duren Sawit East Jakarta, 57 from SDN 02 Bantar Gebang Bekasi, 52 from SDN Cikedokan 01 Kecamatan Cikarang Barat Bekasi and 55 from SDN Cakung Serang. The samples collected had fulfilled the inclusion criteria, aged 6-12 years, had agreed and signed the informed consent sheet. Exclusion criteria included taking worm medicine 6 months earlier and not collecting feces on a predetermined day. Examination of the sample was carried out by the Kato-Katz method. The results of this study indicate that, there is only one school that is positive for helminthiasis, while 4 other schools are negative. At SDN in Serang (Banten) 9 children were found infected with STH or prevalence was 16.4% with mild intensity. The types of STH found were Ascaris lumbricoides (68.75%), Trichuris trichiura (31.25%), and no eggs from Necator americanus. The highest frequency occurs in children aged 6-8 years. There is no significant relationship between the prevalence and rate of STH infection with age and sex.